Synthesis of Secondary and Tertiary Alkyl Boronic Esters by gem‐Carboborylation: Carbonyl Compounds as Bis(electrophile) Equivalents. (12th July 2018) - Shi, Dunfa; Wang, Lu; Xia, Chungu; Liu, Chao
Abstract: An unprecedent gem ‐carboborylation of aldehydes and ketones provides access to various secondary and tertiary alkyl boronic esters. The addition of B2 pin2 to a carbonyl compound generates α‐oxyl‐substituted alkyl boron species. Organolithium and Grignard reagents are then applied as C nucleophiles for the 1, 2‐metalate rearrangement process. The organolithium reagents can also be generated by C−H lithiation or halogen/lithium exchange. The use of chiral ligands led to the generation of chiral alkyl boronic esters in enantioenriched form, demonstrating that the enantioselectivity of this transformation is catalyst‐controlled.